A socioeconomic analysis of joint venture smallholder private treefarm - agroforestry practices by farmers in Kudat - Roslan Abdillah (2005)
A study to assess farmers awareness and adoption of tree farming as an agroforestry innovation in joint venture smallholder private treefarming (JV SPTF) was conducted In the district of Kudat, Sabah. The JV SPTF was introduced by SAFOOA to the farmers in Kudat to help them to overcome the problems of environmental degradation and poverty in the rural area. SAFOOA would provide planting stock and technical advice, and would assure a market for the output at a guaranteed agreed price. The trees planted were Acacia mangium, whereby in Sabah the MAl can reach up to 28-44 cubic meters per hectare per year. The JV SPTF project can provide many benefits to society at large, nevertheless, adoption of JV SPTF will come at a price that is, through political will and the action of many individual farmers. In a survey, a total of 40 farmers were interviewed using a structured questionnaire which focused on awareness, adoption and participation of farmers in JV SPTF project. The importance of government assistance which would limit farmers future adoption was also explored. Majority of the respondents were found to be aware of the concept and benefits of the innovation at all level of farmer's education. The main cause driving the farmers to adopt JV SPTF is children future, and higher profit regardless of full-time or part-time farmer, as examined from the standpoints of financial, biological, and institutional viability of the project. The study also found out that expectation of government assistance is such that, without subsidies of some kind, villagers often will not participate, and when subsidies end, so does participation. Strengthening extension education on tree farming, technical assistance, and financial support can encourage future adoption of tree farming. However, these programs must clearly define the problem and address the concerns and needs of the farmers, are among the recommendations given in this study.